Enhancing Oral Proficiency: Strategies for Improving Speaking and Pronunciation - Dilorom Poyonova; Sevara Abdishukurova; Makhliyo Shomurodova (Scientific Trends, 2025)
This article explores various methodologies and techniques for improving speaking and pronunciation skills in second language acquisition. It examines the efficacy of different approaches, including explicit instruction, communicative activities, technology-assisted learning, and feedback mechanisms, while considering the diverse needs and learning styles of language learners. The article emphasizes the importance of a holistic approach, combining focused practice with opportunities for authentic communication to achieve optimal results.